A comprehensive investigation on the distribution of circulating follicular T helper cells and B cell subsets in primary Sjögren's syndrome and systemic lupus erythematosus. (21st October 2015) - Szabó, K.; Papp, G.; Szántó, A.; Tarr, T.; Zeher, M.
Summary: Follicular T helper (Tfh) cells have a crucial role in regulating immune responses within secondary lymphoid follicles by directing B cell differentiation towards memory B cells and plasma cells. Because abnormal humoral responses are key features in both primary Sjögren's syndrome (pSS) and systemic lupus erythematosus (SLE), the aim of this study was to profile the pathological connection between peripheral Tfh cells and B cells in the two diseases. Twenty‐five pSS patients, 25 SLE patients and 21 healthy controls were enrolled into the study. We determined the ratio of circulating Tfh‐like cells, their interleukin (IL)‐21 production and different B cell subsets by flow cytometry. We observed higher percentages of naive B cells in both diseases, while non‐switched and switched memory B cells showed decreased frequencies. The proportions of double‐negative B cells and plasmablasts were elevated in SLE and decreased in pSS. The percentages of transitional B cells and mature‐naive B cells were higher in SLE. Patients with more severe disease course had an elevated ratio of TFH ‐like cells and increased IL‐21 production. Moreover, expansion of Tfh‐like cells correlated positively with parameters related to antibody secretion, including serum immunoglobulin (Ig)G, immune complexes (ICs) and autoantibodies. Correlation analysis between Tfh‐like cells and certain B cell subsets revealed possible defects during B cell selection. In conclusion, our observations on the profound expansion of circulating Tfh‐like cells and their IL‐21 production, along with the characteristic aberrant peripheral B cell distribution in both pSS and SLE, indicate the prominent role of Tfh cell in the regulation of B cell selection.